Neurogenesis is Enhanced in Young Rats with Genetic Absence Epilepsy: An Immuno-electron Microscopic Study - (:unkn) unknown (TURKISH NEUROSURGICAL SOC, 2021)
AIM: To investigate neurogenesis in both adult and 3-week-old genetic absence epilepsy rats from Strasbourg (GAERS) to determine if newly formed neurons within the dentate gyrus (DG) form synaptic contacts with GABAergic (gamma aminobutyric acid) and glutamatergic nerve terminals and compared to the control (non-GAERS) Wistar rats. MATERIAL and METHODS: Brain tissue was processed for electron microscopic assessment. Thin sections from the hippocampal DG were double-labelled for anti-GABA or anti-VGLUT1 (vesicular glutamate transporter 1) and anti-doublecortin (DCX) antibodies using immunogold methodology and examined with the transmission electron microscope for morphological changes and to quantify the density of gold labeling. RESULTS: DCX immunoreactivity was demonstrated within axon terminals, dendrites and somata in all groups. DCX and GABA or VGLUT1 were found to be co-localized in the axon terminals in all groups. We observed that DCX-immunoreactive (-ir) profiles formed synaptic contacts with GABAergic and glutamatergic terminals. The percentage of DCX labeling in dendrites, compared to axons, and the percentage of DCX-ir terminal profiles forming asymmetrical synapses, compared to those forming symmetrical synapses, were increased in all groups compared to the control group. DCX immunoreactivity in the 21-day-old GAERS group was found to be increased compared to the Wistar group. CONCLUSION: We conclude that newly born neurons are incorporated into the local hippocampal network in both the GAERS and the control Wistar rats. The results suggest that the neurogenesis taking place in the hippocampus may also be involved in the mechanism underlying absence seizures in GAERS.
Keywords: Doublecortin; GABA; VGLUT-1; GAERS; Immunoelectron microscopy; GLUTAMATERGIC GRANULE CELLS; DENTATE GYRUS; GABAERGIC PHENOTYPE; STATUS-EPILEPTICUS; ADULT; NEURONS; DOUBLECORTIN; GABA; EXPRESSION; BORN